A (RE)CONSTRUÇÃO DE CONTEXTOS E CULTURAS DA VELHICE E DO ENVELHECIMENTO: ABORDAGENS DA GERONTOLOGIA SOCIAL/CRÍTICA / A (re)construction of contexts/cultures of old age and ageing: social/critical gerontology approaches (Trabalho & Educação, 2016)
It' understood that the social and critical theory, as well as the processes of it production (f.e., scientific research), are "languages" to objectify a social phenomena. Therefore, both processes shoub be an objecto f reflexivity about the sociocognitive representation of the social phenomena. From these epistemological/methodological prepositions, it's analysed the knowledge from Social/Critical Gerontology by theories of "social use of knowledge" and "double rupture". Thus, it are reviewed some theories about construction and reconstruction of contexts/cultures of old age/ageing in 3rd/4th Ages. From this review, it's concluded: (i) the 3rd/4th Ages and old age/ageing are different categories; (ii) there is a social relationship between political and economical agencies, and the construction and reconstruction of contexts/cultures of old age/ageing in 3rd/4th Ages; (iii) the analyses of spacial/ temporal belongings are an important subject of constrution and reconstrution theories; (iv) there is no single theoritical framework about spacial/temporal belongings, due to the retired elderly agency. ___Entende-se que a teoria social e crítica, assim como os processos da sua reprodução (p.e., a investigação científica), são "linguagens" que objetivam fenómenos da realidade social. Assim, ambos os processos devem ser objetos de reflexividade sobre a representação sociocognitiva desses fenómenos. Neste artigo, parte-se desta preposição epistemológica/metodológica, para interpretar o "uso social do conhecimento" e a "dupla ruptura" do conhecimento produzido pela gerontologia social/crítica. Deste modo, faz-se a revisão de algumas teorias da construção e reconstrução de contextos/culturas da velhice/envelhecimento nas 3a/4a Idades. Com a sua análise, pretende-se argumentar que: (i) as 3a/4a Idades são categorias diferentes das velhices/envelhecimentos; (ii) existe uma relação social entre agências da política e economia e a formação de contextos/culturas da velhice/envelhecimento nas 3a/4a Idades; (iii) as pertenças espaciais/temporais dos/as idosos/as reformados/as são um bom analisador das teorias da construção e da reconstrução; (iv) e não existe um quadro teórico único sobre as pertenças espaciais/temporais devido à capacidade de agência das pessoas idosas reformadas.